Crimes against the State, Crimes against Persons : Detective Fiction in Cuba and Mexico - Braham, Persephone (Book collections on Project MUSE., 2004)
Persephone Braham shows how the Cuban novela negra examines the Revolution through a chronicle of life under a decaying regime, and how the Mexican neopoliciaco reveals the oppressive politics of modernization in Latin America. Considering the work of writers such as Leonardo Padura Fuentes as well as G.K. Chesterton, Braham addresses Marxist critiques of the culture industry and Latin American postmodernity.